2007
DOI: 10.1007/s00024-007-0280-x
|View full text |Cite
|
Sign up to set email alerts
|

Precursory Subsurface 222Rn and 220Rn Degassing Signatures of the 2004 Seismic Crisis at Tenerife, Canary Islands

Abstract: Precursory geochemical signatures of radon degassing in the subsurface of the Tenerife Island were observed several months prior to the recent 2004 seismic-volcanic crisis. These premonitory signatures were detected by means of a continuous monitoring of 222 Rn and 220 Rn activity from a bubbling CO 2 -rich gas spot located at 2.850 m depth inside a horizontal gallery for groundwater exploitation at Tenerife. Multivariate Regression Analysis (MRA) on time series of the radon activity was applied to eliminate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Radon-222 ( 222 Rn) concentrations in soil gas and groundwater have been known to increase abruptly before and/or during large earthquakes in many parts of the world (Hauksson 1981;King 1984/85;Heinicke et al 1995;Igarashi et al 1995;Pérez et al 2007;İnan et al 2008;Kuo et al 2010). The sensitivity of 222 Rn concentration has been confirmed by its response to earthquakes a few hundred kilometers away (Fleischer 1981;Toutain and Baubron 1999;Cicerone et al 2009;Ghosh et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Radon-222 ( 222 Rn) concentrations in soil gas and groundwater have been known to increase abruptly before and/or during large earthquakes in many parts of the world (Hauksson 1981;King 1984/85;Heinicke et al 1995;Igarashi et al 1995;Pérez et al 2007;İnan et al 2008;Kuo et al 2010). The sensitivity of 222 Rn concentration has been confirmed by its response to earthquakes a few hundred kilometers away (Fleischer 1981;Toutain and Baubron 1999;Cicerone et al 2009;Ghosh et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental parameters are critical in modulating radon emissions (e.g., Mogro-Campero and Fleischer, 1977;Pinault and Baurbon, 1996;Pérez et al, 2007;among others).…”
Section: Introductionmentioning
confidence: 99%
“…Recent automatic measurements have shown that environmental parameters are critical in modulating radon emissions (e.g., Pinault and Baurbon, 1996;Zimmer and Erzinger, 2003;Pérez et al, 2007;Cigolini et al, 2009;Laiolo et al, 2012) and CO 2 degassing (Viveiros et al, 2008;Carapezza et al, 2009;Rinaldi et al, 2012). In this paper we will report additional data collected during 2002-2007 at Stromboli volcano.…”
Section: Introductionmentioning
confidence: 99%